Internalizing and Supplicating with the Beautiful Names of Allah A Treatment Intervention for Anxiety in University Students - Bazme, Numerah S (Al Misykat : Journal of Islamic Psychology, 2023)
Purpose: The purpose of this research was to analyze the effect of internalizing and supplicating through Names of Allah on anxiety levels in university students. Inclusion of faith/religion as an intervention is a scientific way of reducing worrisome thoughts. Methods: A pre and post design was administered to measure the anxiety levels before and after participant’s carry out the procedure with the help of the STAI (State-Trait Anxiety Inventory) scale and open-ended questions. Results were analyzed with SPSS using dependent or paired t-test. Results: The study demonstrated that the participants showed statistically significant improvement of their emotional states (anxiety) following the intervention compared to before the intervention took place (p0.001). Hence, indicating that internalizing and supplicating with the names of Allah reduced anxiety in university students as hypothesized. Qualitative results also revealed positive results. Future directions and recommendations are presented in the paper with a focus on furthering the research in this new area. Keywords: Supplication, Names of Allah, Anxiety Levels, Religion, Islamic Psychology